Transition-metal-catalyzed hydrogen-transfer annulations: access to heterocyclic scaffolds - Nandakumar, Avanashiappan; Midya, Siba Prasad; Landge, Vinod Gokulkrishna; Balaraman, Ekambaram (Angewandte Chemie-International Edition, 2015)
The ability of hydrogen-transfer transition-metal catalysts, which enable increasingly rapid access to important structural scaffolds from simple starting materials, has led to a plethora of research efforts on the construction of heterocyclic scaffolds. Transition-metal-catalyzed hydrogen-transfer annulations are environmentally benign and highly atom-economical as they release of water and hydrogen as by-product and utilize renewable feedstock alcohols as starting materials. Recent advances in this field with respect to the annulations of alcohols with various nucleophilic partners, thus leading to the formation of heterocyclic scaffolds, are highlighted herein.

Triazine functionalized porous covalent organic framework for photo-organocatalytic E-Z isomerization of olefins - Bhadra, Mohitosh; Kandambeth, Sharath; Sahoo, Manoj K.; Addicoat, Matthew; Balaraman, Ekambaram; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Visible light-mediated photocatalytic organic transformation has drawn significant attention as an alternative process for replacing thermal reactions. Although precious metal/organic dyes based homogeneous photocatalysts have been developed, their toxic and nonreusable nature makes them inappropriate for large-scale production. Therefore, we have synthesized a triazine and a keto functionalized nonmetal based covalent organic framework (TpTt) for heterogeneous photo catalysis. As the catalyst shows significant absorption of visible light, it has been applied for the photocatalytic uphill conversion of trans-stilbene to cis-stilbene in the presence of blue light-emitting diodes with broad substrate scope via an energy transfer process.

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Tandem acceptorless dehydrogenative coupling-decyanation under nickel catalysis - Midya, Siba P.; Subaramanian, Murugan; Babu, Reshma; Yadav, Vinita; Balaraman, Ekambaram (Journal of Organic Chemistry, 2021)
The development of new catalytic processes based on abundantly available starting materials by cheap metals is always a fascinating task and marks an important transition in the chemical industry. Herein, a nickel-catalyzed acceptorless dehydrogenative coupling of alcohols with nitriles followed by decyanation of nitriles to access diversely substituted olefins is reported. This unprecedented C=C bond-forming methodology takes place in a tandem manner with the formation of formamide as a sole byproduct. The significant advantages of this strategy are the low-cost nickel catalyst, good functional group compatibility (ether, thioether, halo, cyano, ester, amino, N/O/S heterocycles; 43 examples), synthetic convenience, and high reaction selectivity and efficiency.